Data for: Impact of unusually wet permafrost soil on understory vegetation and CO2 exchange in a larch forest in eastern Siberia - Kotani, A (via Mendeley Data) (2018)
Monthly CO2 flux by eddy covariance in a larch forest in eastern Siberia THIS DATASET IS ARCHIVED AT DANS/EASY, BUT NOT ACCESSIBLE HERE. TO VIEW A LIST OF FILES AND ACCESS THE FILES IN THIS DATASET CLICK ON THE DOI-LINK ABOVE